The numbing effect of experience - Giordano, Frank (Kansas State University, 2019)
Job experience is a pervasive metric used in human resource functioning; however, its predictive validity might not be as intuitive as it seems especially regarding safety outcomes. While research suggests a positive relationship between experience and performance (McDaniel, Schmidt, & Hunter, 1988; Sturman, 2003), there are instances when experience may have a null or negative relationship with performance (Woltz et al., 2000). Specifically, this occurs when the perceived similarity between prior experience and a new task is actually discrepant. Also, rigidities in problem-solving can form from job experience, leading to impaired performance (Dokko, Wilk, & Rothbard, 2009; Bilalić, McLeod, & Gobet, 2008). The relationship between job experience and safety outcomes is more intricate. Self-appraisals of safety performance can be discrepant, which is problematic when tasks include safety behaviors that individuals assume they can adequately enact. The means of informing self-efficacy can also be inequitable, such that positive safety behavior feedback (e.g., no injury or accident) can go ungiven or unnoticed, while performance feedback is often a focus of organizations (Gun, 1993). This might contribute to the false perception of similarity in discrete job tasks and safety behaviors (i.e., task performance vs. safety performance). Individuals can be exposed to work experiences which do not provide adequate opportunities to discern work system components, inherent hazards, and risks. This study aims to observe the effect prior experience has on performance of a task, the execution of safety behaviors, and participants’ appraisals of their self-efficacy regarding both the task and their safety behaviors.
Keywords: Experience; Self-efficacy; Task performance; Safety